‫الخيارات ‬‫التمويلية‬ ‫و‬ ‫إنعاكساتها‬ ‫على‬ ‫قيمة‬ ‫المؤسسة‬ ‫المسعرة‬ ‫في‬ ‫البورصة‬ ‫دراسة‬‫حالة‬ ‫مؤسسة‬ ‬‬‫nca)الرويبة2011-2014 - ‬‫رحمة‫ قواسمية ‬; عبلة ‫شبوط‬‫ ‬ (My University, 2018)
The main objective of all economic society is to create or to maximize its value by optimizing sources of financing available within acceptable cost and yield limits. Therefore, this study aims to know the impact of the options of financing on the value of the listed establishment, and for achieve the aim of this study and answer all these questions, we have carry out a descriptive approach to the latter, but from the side practice we chose a national company (NCA) Rouiba, and we applied this approach for the period (2011-2014), which allowed us to estimate the value of this company before and after its get into the mix and know the effect of financing constraints on the latter, and this by using financing indicators of the company during this period. In conclusion, this study allowed us to demonstrate that rouiba was unable to hedge its bond exchanges after entering the stock exchange and that the treasurer remained in deficit, and also the drop in ratios financial, which forces this Rouiba company to diversify sources of financing to cover expenses and increase its value. .................................................. الهدف الرئيسي لأي مجتمع اقتصادي هو إنشاء أو لتعظيم قيمتها من خلال تحسين مصادر التمويل متاحة ضمن حدود التكلفة والعائد المقبولة. ولذلك تهدف هذه الدراسة إلى معرفة أثر خيارات التمويل بقيمة المنشأة المدرجة و تحقيق هدف هذه الدراسة والإجابة على كل هذه الأسئلة لدينا تنفيذ نهج وصفي لهذا الأخير، ولكن من الجانب الممارسة اخترنا الشركة الوطنية (NCA) الرويبة، و وقد طبقنا هذا المنهج للفترة (2011-2014) والذي سمح لنا بتقدير قيمة هذه الشركة قبل وبعد تأسيسها ادخل إلى هذا المزيج واعرف تأثير قيود التمويل عليه الأخير، وذلك باستخدام مؤشرات التمويل الشركة خلال هذه الفترة. في الختام، أتاحت لنا هذه الدراسة إثبات أن الرويبة لم تكن قادرة على التحوط في بورصات السندات بعد دخول البورصة و أن أمين الصندوق بقي في العجز، وكذلك انخفاض النسب المالية، الأمر الذي يجبر شركة الرويبة على تنويع مصادرها التمويل لتغطية النفقات وزيادة قيمتها.
‬